PROKRASTINASI AKADEMIK MAHASISWA DALAM PENCAPAIAN TARGET ASUHAN KEBIDANAN - Ni Nyoman Ayu Dwi Astini (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
Research team. Description of Academic Procrastination in Achieving Target of Midwifery Care for Sixth Semester Students of Study Program DIII FOK Undiksha Midwifery. Keywords: Academic Procrastination in Achieving midwifery care targets. This study aims to find out the description of academic procrastination in achieving the target of care for midwifery. This research was conducted on the students of the D3 Kebidanan FOK Undiksha Study Program, a descriptive study. Instrument in the form of an academic procrastination questionnaire. The research sample consisted of 82 students in the sixth semester and the whole was used as respondents. Based on the results of the calculation of descriptive analysis, the mean data = 76.39; median = 76.50; standard deviation = 11.05; range = 43.00; minimum score of 54.00; maximum score = 97.00. To determine the tendency of academic procrastination in achieving the target of midwifery care, first the ideal mean (Mi) and ideal standard deviation (Sdi) are calculated. Based on the results of the calculation, the classification of academic procrastination scores in the achievement of midwifery care targets, a high category of 13 people (15.85%), a category of 40 people (48.80%), and a low category of 29 people (35.35 %). Thus, it can be concluded that the description of academic procrastination in achieving the target of midwifery care for the Dika Midwifery D3 Study Program students in 2018 is sufficient.